2014
DOI: 10.3390/en7128076
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Data-Driven Fast Capacity Estimation of Spent Electric Vehicle Lithium-ion Batteries

Abstract: Fast capacity estimation is a key enabling technique for second-life of lithium-ion batteries due to the hard work involved in determining the capacity of a large number of used electric vehicle (EV) batteries. This paper tries to make three contributions to the existing literature through a robust and advanced algorithm: (1) a three layer back propagation artificial neural network (BP ANN) model is developed to estimate the battery capacity. The model employs internal resistance expressing the battery's kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…Hybrid models: Combining models Kalman filter [6,9] and data to achieve High cost for model development Particle filter (PF) [7,8] a better performance Data-driven approach Neural networks [11,12,18] Simple Large amount of data are required Gaussian process regression (GPR) [13] Relevance vector machine (RVM) [14] Practical Only for short-term prediction SVR and PF [15] High accuracy Hybrid approach GPR and PF [16] Combines advantages Complex RVM and PF [17] of different approaches…”
Section: Algorithms/methods Advantages Disadvantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid models: Combining models Kalman filter [6,9] and data to achieve High cost for model development Particle filter (PF) [7,8] a better performance Data-driven approach Neural networks [11,12,18] Simple Large amount of data are required Gaussian process regression (GPR) [13] Relevance vector machine (RVM) [14] Practical Only for short-term prediction SVR and PF [15] High accuracy Hybrid approach GPR and PF [16] Combines advantages Complex RVM and PF [17] of different approaches…”
Section: Algorithms/methods Advantages Disadvantagesmentioning
confidence: 99%
“…These model-based approaches can achieve high estimation accuracy, but they also require heavy work in the model development. For the data-driven approach [11][12][13][14], it is not necessary to understand the degradation principle of the battery; it only uses degradation data to build the degradation model. For example, Rezvani et al [12] used an adaptive neural network (ANN) and linear prediction error method for the SOH quantification of a lithium-ion battery.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high temperature can cause degradation, despite its ability to temporarily increase the battery performance. Li et al [27] demonstrated that the internal temperature of a battery Energies 2015, 8,[12439][12440][12441][12442][12443][12444][12445][12446][12447][12448][12449][12450][12451][12452][12453][12454][12455][12456][12457] not only functions as a safety precaution, but also provides external characteristic information, which can be utilized to assess the decrease in battery capacity. Figure 3 depicts the changes in the charge and discharge temperature of battery 7 in 168 cycles.…”
Section: Average Temperatures During Charge and Discharge (F 4 And F 5 )mentioning
confidence: 99%
“…In MKRVM, each kernel function is a linear combination of different basic kernels. A typical multi-kernel function is a combination of a radial basic function (RBF) kernel and a polynomial kernel Energies 2015, 8,[12439][12440][12441][12442][12443][12444][12445][12446][12447][12448][12449][12450][12451][12452][12453][12454][12455][12456][12457] because the former is local and the latter is global. Given a set of N observations x i (i = 1, 2, .…”
Section: Multi-kernel Relevance Vector Machinementioning
confidence: 99%
See 1 more Smart Citation